Effect of Time Duration on Bacterial Colonization in Double ‘J’ Stent after Ureteroscopy and Intracorporeal Pneumatic Lithotripsy in Adult (Bangladesh Journal of Urology, 2022)
Introduction: Ureteric stone disease is common all over the world. Because of advancements in endourology and instruments- urologists manage ureteral stone effectively by ureteroscopy and lithotripsy using various energy sources. Commonly, lower ureteric stones are managed by ureteroscopy and intracorporeal pneumatic lithotripsy (URS and ICPL). After completing the procedure surgeons prefer to install double J (DJ) stent for a variable period within the ureter to overcome ureteral edema. There is no guideline for the optimal duration of keeping DJ stent in ureteral lumen. Urologists decide the duration of DJ stent according to their clinical experience & judgment- that makes a wide variation of stent period. Keeping the double J (DJ) stent for a longer duration may produce harmful effects, those even may be life-threatening.Objective: To observe the effect of time duration on bacterial colonization in DJ stent after URS and ICPL.Material and method: This experimental study was conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), for 1-year duration. The total sample size was 82. Samples were allocated into two groups. In group A: Double J stent was kept in situ for d” 4 weeks, whereas in Group B: stent duration was > 4 (up to 8) weeks. In this study, purposive sampling technique was implemented. Unilateral ureteral stone managed by URS, ICPL were included in the study. Patients having bilateral stones, co-morbidities like diabetes mellitus (DM), malignancy, immunosuppression, chronic kidney disease (CKD), and who had per operative ureteral injury were excluded. After removal of the DJ stent, 2-3 cm bladder-end tip was sent for culture and sensitivity. Reports were collected and documented.Result: Out of 82 cases, 40 were in group A and 42 in group B. 62 patients were male, 20 were female. DJ stent culture was positive in 14 cases (17%), whereas urine culture was positive in 7cases (8.5%). Among those- both stent and urine were positive in 4 cases (4.8%). Stent positive but urine negative in 10 cases (71%). In positive cases, stent and urine were colonized by a similar organism. E. coli was the commonest causative organism. Stent culture was positive in 4 cases (28.6%) in group A, 10 cases (71.4%) in group B but it was statically insignificant (p-value 0.09).Conclusion: Bacterial colonization in DJ stent increases with longer indwelling time. Individually stent or urine culture can not detect all pathogens in the urinary tract. So urine culture, as well as stent culture, is required to detect the uropathogen. The final recommendation is that-removal of DJ stent as early as possible is the key to prevent bacterial colonization.Bangladesh J. Urol. 2021; 24(2): 188-192